2022
DOI: 10.3389/fphar.2022.811372
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Regulates Alveolar Macrophage Polarization to Protect Against Acute Lung Injury in Rats Caused by Paraquat Poisoning

Abstract: This study explored the role of metformin (MET) in regulating the polarization of alveolar macrophages to protect against acute lung injury (ALI) in rats caused by paraquat (PQ) poisoning. The in vivo studies showed that the 35 mg/kg dose of MET increased the survival rate of rats, alleviated pathological damages to the lungs and their systemic inflammation, promoted the reduction of the pro-inflammatory factors interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) levels, and increased the anti-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Then, we screened, reviewed, and excluded most of these articles as not meeting our criteria stated in the method section. Finally, we included 15 preclinical studies ( Zmijewski et al, 2008 ; Jian et al, 2013 ; Liu et al, 2016 ; Vaez et al, 2016 ; Wang et al, 2016 ; Ghavimi et al, 2018 ; Wu et al, 2018 ; Yu et al, 2018 ; He et al, 2019 ; Wu et al, 2019 ; Xian et al, 2021 ; Zhang Y. et al, 2022 ; Zhang M. et al, 2022 ; Yuan et al, 2022 ; Wan et al, 2023 ) in this meta-analysis. The procedure for study selection is presented in a flow chart in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we screened, reviewed, and excluded most of these articles as not meeting our criteria stated in the method section. Finally, we included 15 preclinical studies ( Zmijewski et al, 2008 ; Jian et al, 2013 ; Liu et al, 2016 ; Vaez et al, 2016 ; Wang et al, 2016 ; Ghavimi et al, 2018 ; Wu et al, 2018 ; Yu et al, 2018 ; He et al, 2019 ; Wu et al, 2019 ; Xian et al, 2021 ; Zhang Y. et al, 2022 ; Zhang M. et al, 2022 ; Yuan et al, 2022 ; Wan et al, 2023 ) in this meta-analysis. The procedure for study selection is presented in a flow chart in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…As metformin has shown its role in reducing mortality in septic patients ( Li et al, 2021 ; Gómez et al, 2022 ), it is possible that metformin may also benefit ARDS. A number of preclinical studies have highlighted the effect of metformin on acute lung injury (ALI), a mild form of ARDS ( Wu et al, 2019 ; Medeiros et al, 2021 ; Xian et al, 2021 ; Yuan et al, 2022 ). Reduced mortality, pulmonary wet-to-dry weight ratio (W/D), lung injury scores, protein in bronchoalveolar lavage fluid, and levels of malondialdehyde (MDA) as well as myeloperoxidase (MPO) in the lungs were announced in those studies.…”
Section: Introductionmentioning
confidence: 99%
“…This study also highlighted the protective effect of metformin in SARS-CoV-2 induced pulmonary inflammation in hACE2 transgenic mice. Furthermore, metformin treatment alleviated paraquet-induced lung inflammation by promoting alveolar macrophages’ polarization towards M2 ( Yuan et al, 2022 ). Furthermore, many studies have suggested that metformin exerts vascular protective effect on ECs.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is a commonly used medication for diabetes. Metformin treatment has been shown to increase M2 macrophages and decrease M1 macrophages [120][121][122][123][124][125], likely through NLRP3 inflammasome Macrophages as a Target for Treating Diabetic Foot Ulcers DOI: http://dx.doi.org/10.5772/intechopen.106613 suppression, which was discussed above [123]. Melatonin is a medication not for diabetes.…”
Section: Strategies To Improve Diabetic Wound Healing Through Manipul...mentioning
confidence: 99%